2019
DOI: 10.3390/ma12152345
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Rheological Behaviors of Styrene-Butadiene-Styrene/Crumb Rubber Composite Modified Bitumen after Different Long-Term Aging Processes

Abstract: In this study, a new type of composite modified bitumen was developed by blending styrene-butadiene-styrene (SBS) and crumb rubber (CR) with a chemical method to satisfy the durability requirements of waterproofing material in the waterproofing layer of high-speed railway subgrade. A pressure-aging-vessel test for 20, 40 and 80 h were conducted to obtain bitumen samples in different long-term aging conditions. Multiple stress creep recovery (MSCR) tests, linear amplitude scanning tests and bending beam rheomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…e viscous flow properties of the samples were measured within a large range (10 −3 to 10 1 s −1 ) of shear rates at 60°C. e creep behaviours of the high-viscosity asphalt at a low temperature were characterized by applying a bending beam rheometer (BBR) to attain two indices, creep stiffness S and the rate of change m of the stiffness with time [23]. By using the time-temperature equivalence principle, the viscoelasticity within wide frequency and temperature ranges was acquired.…”
Section: Rheological Testmentioning
confidence: 99%
“…e viscous flow properties of the samples were measured within a large range (10 −3 to 10 1 s −1 ) of shear rates at 60°C. e creep behaviours of the high-viscosity asphalt at a low temperature were characterized by applying a bending beam rheometer (BBR) to attain two indices, creep stiffness S and the rate of change m of the stiffness with time [23]. By using the time-temperature equivalence principle, the viscoelasticity within wide frequency and temperature ranges was acquired.…”
Section: Rheological Testmentioning
confidence: 99%
“…The magnitude of the value characterizes the sensitivity of the Jnr of the asphalt binder to the action of heavy loads. Its larger value means that the binder is more sensitive to heavy load traffic and its creep recovery ability is poor [ 31 ]. The calculated results show that although the values of some groups do not show a consistent trend, it is undeniable that the values of increase to varying degrees when the amount of MMT is increased.…”
Section: Resultsmentioning
confidence: 99%
“…Fowkes demonstrated that the dispersion force between liquid and solid can be expressed as the liquid–solid surface free energy dispersion component [ 31 ]. Owens developed this approach and made it applicable to polar components [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Asphalt concrete has been tentatively used for a full-cross-section waterproofing layer in the substructure of ballastless track in China [1,2]. Asphalt concrete has also been employed as an isolation layer of the high-speed railway foundation, sub-ballast layer of ballast railway, or reinforcement layer of the railway subgrade in Germany, Japan, France, Italy, etc.…”
Section: Introductionmentioning
confidence: 99%